Effects of Inspiratory Muscles Training Plus Rib Cage Mobilization on Chest Expansion, Inspiratory Accessory Muscles Activity and Pulmonary Function in Stroke Patients - Shin Jun Park (Applied Sciences, 2020)
After stroke, limited ribcage movement may lead to impaired respiratory function. Combining threshold inspiratory muscle training with rib cage joint mobilization has been shown to enhance the recovery of respiratory function in patients with stroke. The present study investigated whether the combination of rib cage joint mobilization and inspiratory muscle training would improve chest expansion, inspiratory muscle activity, and pulmonary function after stroke. Thirty stroke patients were recruited and randomly assigned to one of the two groups, namely 6-week rib cage joint mobilization with inspiratory muscle training (experimental group) or inspiratory muscle training alone (control group). Outcome measures included upper and lower chest expansion, activity of accessory inspiratory muscles (latissimus dorsi (LD) and upper trapezius (UT)), and pulmonary function (forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1), and peak expiratory flow (PEF)). All evaluations were conducted at baseline and after 6 weeks of inspiratory muscle training. Significant increases were observed in upper and lower chest expansion, LD and UT muscle activity, FVC, FEV1, and PEF in both the groups. Upper and lower chest expansion and muscle activity of UT and LD were significantly higher in the experimental group than in the control group. No significant differences were observed in FVC, FEV1, and PEF between the groups. Inspiratory muscle training is effective in improving chest expansion, inspiratory muscle activity, and pulmonary function after stroke. The addition of rib cage joint mobilization further increases chest expansion and inspiratory muscle activity.